Ritual Language in Osing Cultural Ceremonies: A Sociolinguistic Study of Speech Genre in Seblang Ritual in Olehsari - Nur Izahaslina; Muhammad Hasbullah Ridwan (Jurnal Sastra Indonesia, 2026)
Representations of women in using qualitative methods and an ethnographic communication approach, this study aims to explain the form, function, and context of ritual language in the seblang ceremony in the Osing community in Olehsari. Data were analyzed using Dell Hymes' SPEAKING model after being collected through documentation, observation, and interviews. According to the research findings, ritual language has archaic, symbolic, and formal characteristics and also serves to communicate spiritually, strengthen cultural values, and preserve traditions. In addition, the circumstances of speech, the speakers, and cultural norms influence its meaning. According to the research results, the seblang ritual language represents the living cultural identity of the Osing community.